Estimating the Pulmonary Artery Pressure: Transthoracic Echocardiography vs. Right Heart Catheterization - S. Houssein , Mohamed; Elbraky , Fathi (Libyan Journal of Public Health Practices, 2024)
Pulmonary hypertension is defined as a mean pulmonary artery pressure (MPAP) ≥ 20 mmHg at rest, measured by right heart catheterization (RHC). The accuracy of measuring PH without invasive procedures remains a challenging task. The current study was aiming to evaluate the correlation between transthoracic echocardiography (TTE) and RHC in estimating pulmonary artery pressure (PAP) and to assess whether TTE can be a reliable tool for diagnosing and following up with patients with PH. This is a cross-sectional study of 29 patients seen at Benghazi Medical Centre diagnosed with PH in order to compare invasively measured PAP to estimated PAP by TTE. The mean age of the patients was 45.6±16.2 years, with female predominance (86.21%). RHC confirmed PH in 26 patients (89.8%), while 3 patients (10.2%) had normal PAP. The mean PAP estimated by TTE was 68.2±26.9 mmHg, significantly higher than that measured by RHC (46.31±26.2 mmHg, p < 0.05). Primary PAH was the leading cause of PH, followed by cardiac etiologies. TTE showed a sensitivity close to 100%, a specificity of 50%, and an overall accuracy of 90.6% in estimating PAP compared to RHC. The Pearson correlation coefficient between PAP measured by RHC and TTE was 0.692 (p < 0.0001). These findings suggest that TTE might be a valuable non-invasive tool for diagnosing and monitoring PH, though caution is warranted due to the variability observed in specific measurements compared to RHC.